Implementasi Pembelajaran PPKn Berbasis Kurikulum Merdeka di SMAN 4 Mataram - Triwibowo, Ragil; Sumardi, Lalu; Fauzan, Ahmad (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The purpose of this study is to ascertain how PPKn learning is implemented at SMAN 4 Mataram based on the autonomous curriculum. This study employs a qualitative methodology in the form of a case study. The informants in this research are the The principal, deputy principal for curriculum, PPKn teacher and class X students. A combination of documentation, interviewing, and observational methods were used to gather data. Data reduction, data presentation, and conclusion-making are the three phases of the Miles and Huberman approach, which was used to conduct the data analysis. The findings of this study showed that SMA Negeri 4 Mataram used PPKn learning based on the Merdeka Curriculum was grouped into 3, namely 1) learning planning consisting of Learning Objective Flow (ATP) and Teaching Modules, 2) implementation of learning consisting of learning with a differentiated approach. , Project for Strengthening the Pancasila Student Profile (P5) and Problem Based Learning (PBL) Learning Model, 3) Evaluation or learning assessment which consists of diagnostic assessments carried out by observation, self-assessment and assessment between friends, formative which is carried out with resume assignments, written tests and quizzes and summative which is carried out with Mid-Semester Tests (UTS)/Mid-Semester Summative (STS) and Mid-Semester Tests (UAS)/Final Semester Summative Tests (SAS) which are carried out online using gadgets.